Evaluating the EAPC Madrid Charter on volunteering in hospice and palliative care: Reflections on impact. (4th May 2022) - Vanderstichelen, Steven; Pelttari, Leena; Scott, Ros
Abstract : The European Association for Palliative Care (EAPC) Madrid Charter on volunteering in hospice and palliative care (HPC) was launched in 2017 to advocate for the support, recognition, promotion and development of volunteering in HPC. However, charters are rarely evaluated, and impact often assumed a priori. To evaluate whether such declarations influence change, we must understand their reach and use. We aimed to assess the awareness, reach and impact of the EAPC Madrid Charter on HPC Volunteering in Europe and evaluate its potential as an advocacy tool in HPC. An online survey questionnaire including open and closed questions, was sent to a convenience sample of all 55 EAPC member organizations, other regional and national European HPC and HPC volunteering organizations. Forty-six responses were received from 11 countries. The Charter mainly spread through word of mouth (72%). Sixty-four per cent of respondents had heard of the Charter; of these 80% had signed it but only 30% had used it. Directors used the Charter in policy documents (70%). Volunteer coordinators had used it in various ways (57%). Most general coordinators (83%) found no use for the Charter. Feedback from participants indicated a lack of practical applications. The Charter was considered useful for policy negotiation but lacking practical applications to support HPC volunteering in the short term. Charters may be tools for long-term change, rather than immediate change in practice. A multipronged approach may be required where Charters are complemented by practical instruments.